Visitors to Vale do Tua Regional Natural Park in northeast Portugal: a cluster segmentation analysis - Lopes, Luisa (2023)
Tourism plays an important role in many economies, and in Portugal, protected areas (PA) have had a strong impact in terms of tourist and economic attractiveness. This study identifies visitors of a Portuguese protected area (PPA), the Vale do Tua Regional Natural Park (PNRVT), based on benefit segmentation. It addresses the following research questions: what are the possible PNRVT market segments? What is the profile of each segment? What motivates each group to visit the PNRVT? It seems important to know the perceptions and profile of potential visitors to PNRVT understanding their motivations and the importance given to resources, activities, equipment, and services they desire. For these purposes, data were collected through a self-administrated questionnaire and multivariate statistics techniques (hierarchical and K-means cluster analysis) were applied, reaching a convenience sample of 395 respondents. From the results obtained, it is possible to conclude that visitors of the PPAs aim to see nature, landscape, flora, fauna, and pedestrian paths. Concerning the PNRVT, five distinct segments of visitors were identified, based on the resources, activities, equipment, and services as desired benefits and further characterized by the motivation for their visit, the frequency of visit, and their sociodemographic profiles. In practice, the present investigation contributes by helping public and private institutions and companies to improve their tourism offerings and develop more efficient marketing plans.